2011
DOI: 10.4049/jimmunol.1100159
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis, Pathway Analysis, and Consomic Mapping Show Genetic Variants of Tnni3k, Fpgt, or H28 Control Susceptibility to Viral Myocarditis

Abstract: Coxsackievirus B3 (CVB3) infection is the most common cause of viral myocarditis. The pathogenesis of viral myocarditis is strongly controlled by host genetic factors. Although certain indispensable components of immunity have been identified, the genes and pathways underlying natural variation between individuals remain unclear. Previously, we isolated the viral myocarditis susceptibility 1 (Vms1) locus on chromosome 3, which influences pathogenesis. We hypothesized that confirmation and further study of Vms1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…However, not all studies have demonstrated that elevated IFN-β correlates with protection in acute CVB3-induced myocarditis. For example, analysis of resistant B10.A and susceptible A/J mice revealed a relationship between higher cardiac viral titer in the first 4 days after infection and increased serum IFN-β expression [50], a finding that is similar to our observations in the Unc93b1 Letr/Letr model. TLR3 deficiency significantly increased mortality and serum viral load, but did not affect cardiac IFN-β expression at day 3 after infection [11].…”
Section: Discussionsupporting
confidence: 83%
“…However, not all studies have demonstrated that elevated IFN-β correlates with protection in acute CVB3-induced myocarditis. For example, analysis of resistant B10.A and susceptible A/J mice revealed a relationship between higher cardiac viral titer in the first 4 days after infection and increased serum IFN-β expression [50], a finding that is similar to our observations in the Unc93b1 Letr/Letr model. TLR3 deficiency significantly increased mortality and serum viral load, but did not affect cardiac IFN-β expression at day 3 after infection [11].…”
Section: Discussionsupporting
confidence: 83%
“…142,143 This led to the identification of several susceptibility genes including IFN-related genes (Fpgt, H28, and Tnni3k). 144 In acute viral coxsackievirus B-induced myocarditis, IFN-α and IFN-β (type I interferons) are important mediators of a Th1 response and reduced viral replication, whereas IFN-γ (type II interferon) regulates monocyte mobilization and fibrosis. 145,146 A mouse model of limited IFN-β activity, induced by knocking out the TRIF protein, had severe chronic myocarditis and dilated cardiomyopathy.…”
Section: Infectious Viral Myocarditismentioning
confidence: 99%
“…In the mouse, TNNI3K has been identified as a potentially important gene in host response to viral cardiomyopathies caused by Coxsackie B virus. 12 In this context, the murine allele with normally, high TNNI3K expression seems to confer a protective role in viral cardiomyopathy. Apart from response to cardiac injury, recent human genetic studies have suggested an intriguing role for TNNI3K in the development of obesity.…”
Section: Abraham and Marchukmentioning
confidence: 99%